Sepsis, leukocytes, cytokines and disseminated intravascular coagulation - Ramazan Çöl; Zafer Durgun (Eurasian Journal of Veterinary Sciences)
Leukocytes play an important rote on the pathogenesis of sepsis-induced disseminated intravascular coagulation. Despite the beneficial role ol leukocytes in host delence, these cells may also cause the initation and progression ol tissue injury in sepsis. Cytokines such as tumor necrosis factor* a (TNF-a) and inlerleukin-1 3 (IL-1 P) activate monocytes, neutrophils and endothelial cells. Inflammatory cytokines initate coagulation mechanism by converting endothelium from an antithrombotic surface to a prothrombotic surface. These cytokines activate both the extrinsic and intrinsic coagulation system by stimulating tissue (actor production. Moreover, they activate neutrophils to release inflammatory mediators such as neutrophil elestase and oxygen free radicals. Various pathogenic effects thai occur in sepsis are attributed to the release of oxygen radicals and enzymes from neutrophils. This review present information about leukocytes and their important roles in sepsis.